KESEHATAN MENTAL PEMUDA: SEBUAH KAJIAN EKONOMI - A.A.I Nirmala Trisna (Puslit Kependudukan dan Pengembangan SDM Universitas Udayana, 2006)
Government of Indonesia has not yet put youth?s mental health as priority in the agenda of health and human resources development. Currently, national health development strategy is on maternal, neonatal and child. The impact on health intervention gap during human?s life cycle is high tendency of youth with unstable mentality, which will lead to diminishing quality of human resources in Indonesia. The paper aims to demonstrate the significancy of lacking intervention program on youth?s mental health. Analysis should benefit stakeholders of human resources as basis for advocacy, decision making and policy design. Method that is applied in the paper is cost utility analysis with social perspective on suicide cases in Sanglah Hospital, Bali. Outcomes of interventions are measured by Quality-Adjusted Life Years (QALYs). Two empirical alternatives are presented in the analysis, i.e. with preventative intervention and no intervention at all. Without intervention, prevalence of suicide case is estimated 9 per 100,000 youths, with total cost of almost Rp 238.9 million and lost of 146.25 QALYs. With intervention, estimated prevalence of suicide case is reduced to 2.25 per 100,000 pemuda, with total cost of almost Rp 2.3 billion and lost of 36.56 QALYs. Cost utility analysis yields cost-utility ratio of Rp 18,5 milion. The analysis indicates that intervention program is more effective than leaving youth to develop without having skills to manage stress. Thus, youth?s mental health should start to be policy priority as it is one effective solution to intervene the diverse health problems of youth. Yet, prime movers are required to accumulate political commitments and to collaborate various programs among stakeholders of human resources, e.g. government, private sector, community and family.